An Assessment on The Capacity Development of Urban Government in Bukidnon in The Implementation of the National HIV/AIDS Policy - Angelita I Jacobe; Marjorie T Sobradil (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2017)
This study is designed to investigate how far the local urban governments of Valencia City and Malaybalay City have developed community support for the care and treatment of HIV/AIDS, done interventions and actions for community understanding, execute mobilization and allocation of funds to combat HIV/AIDS and provide facilities capable of providing interventions for prevention and medical treatment for HIV/AIDS patients. The LGUs of Malaybalay and Valencia have adopted steps to moderate the spread of HIV and AIDS in their localities. These urban governments of Bukidnon had created each an HIV Council that is guided by the principles of mainstreaming HIV responses in the local government plans and multi-sector involvement in the planning, execution and monitoring of the response. This local response is a key element of the country's program for combating HIV. The two local governments (LGUs), along with Cagayan De Oro City, are the core of the program in Region ten. They had committed to reduce HIV infection through the Millennium Development Goal (MDG) and the HIV and AIDS Medium-Term Plan (AMTP).